2006
DOI: 10.1007/s10661-006-9296-4
|View full text |Cite
|
Sign up to set email alerts
|

Spatial & temporal variations of PM10 and particle number concentrations in urban air

Abstract: The size of particles in urban air varies over four orders of magnitude (from 0.001 microm to 10 microm in diameter). In many cities only particle mass concentrations (PM10, i.e. particles <10 microm diameter) is measured. In this paper we analyze how differences in emissions, background concentrations and meteorology affect the temporal and spatial distribution of PM10 and total particle number concentrations (PNC) based on measurements and dispersion modeling in Stockholm, Sweden. PNC at densely trafficked k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
99
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 171 publications
(109 citation statements)
references
References 37 publications
9
99
0
1
Order By: Relevance
“…Mobile measurements on pavements with different maximum stone size but the same mineral composition indicate that smaller stone size gives rise to higher emissions if studded tires are used, but the differences are small and more tests are needed (Johansson et al, 2007b). Laboratory studies using a road simulator showed that there are large differences between different pavement rock materials and maximum stone sizes, especially when using studded tires in the tests.…”
Section: Denier Van Der Gon Et Al / Journal Of the Air And Waste Managmentioning
confidence: 99%
“…Mobile measurements on pavements with different maximum stone size but the same mineral composition indicate that smaller stone size gives rise to higher emissions if studded tires are used, but the differences are small and more tests are needed (Johansson et al, 2007b). Laboratory studies using a road simulator showed that there are large differences between different pavement rock materials and maximum stone sizes, especially when using studded tires in the tests.…”
Section: Denier Van Der Gon Et Al / Journal Of the Air And Waste Managmentioning
confidence: 99%
“…Brake wear and wear of the road surface is an important factor for the highest concentrations in the coarse mode (Manoli et al, 2002). The contribution to particulate mass ranges from place to place from a few percent up to 80% (Almeida et al, 2005;Johansson et al, 2007). It was also found that the traffic contribution in the coarse size fraction (1.9e72 mm) was approximately 80% up to 150 m from the road, it dropped abruptly by a factor of 2 over a distance of 150e200 m and declined further to 20% at 1500 m from the road (Wrobel et al, 2000).…”
Section: Urban Scalementioning
confidence: 99%
“…During dry periods in winter and early spring, abraded pavement and sand are ejected into the air by vehicle turbulence and cause particle concentrations to vastly exceed the environmental quality standard set for inhalable particles (Johansson et al, 2007). This standard is valid for PM 10 and stipulates that the daily mean concentration must not exceed 50 µg m -3 more than 35 days a year and the yearly mean must not exceed 40 µg m -3 (EU, 1999).…”
Section: Introductionmentioning
confidence: 99%